Oculomotor, Vestibular, and Reaction Time Effects of Sports-Related Concussion: Video-Oculography in Assessing Sports-Related Concussion. Issue 3 (May 2019) - Kelly, Kevin M.; Kiderman, Alex; Akhavan, Sam; Quigley, Matthew R.; Snell, Edward D.; Happ, Erik; Synowiec, Andrea S.; Miller, Eric R.; Bauer, Melissa A.; Oakes, Liza P.; Eydelman, Yakov; Gallagher, Charles W.; et al.
Abstract : Objective: The purpose of the study was to test the ability of oculomotor, vestibular, and reaction time (OVRT) metrics to serve as a concussion assessment or diagnostic tool for general clinical use. Setting and Participants: Patients with concussion were high school-aged athletes clinically diagnosed in a hospital setting with a sports-related concussion ( n = 50). Control subjects were previously recruited male and female high school student athletes from 3 local high schools ( n = 170). Design: Video-oculography was used to acquire eye movement metrics during OVRT tasks, combined with other measures. Measures were compared between groups, and a subset was incorporated into linear regression models that could serve as indicators of concussion. Measures: The OVRT test battery included multiple metrics of saccades, smooth pursuit tracking, nystagmoid movements, vestibular function, and reaction time latencies. Results: Some OVRT metrics were significantly different between groups. Linear regression models distinguished control subjects from concussion subjects with high accuracy. Metrics included changes in smooth pursuit tracking, increased reaction time and reduced saccade velocity in a complex motor task, and decreased optokinetic nystagmus (OKN) gain. In addition, optokinetic gain was reduced and more variable in subjects assessed 22 or more days after injury. Conclusion: These results indicate that OVRT tests can be used as a reliable adjunctive tool in the assessment of concussion and that OKN results appear to be associated with a prolonged expression of concussion symptoms.